DESKRIPSI MOTIVASI BERPRESTASI SISWA KELAS XI SMK KESEHATAN REFORMASI PONTIANAK - Darius Darius; Yuline Yuline; Purwanti Purwanti (Universitas Tanjungpura, 2021)
ABSTRACTThis study aims to analyze the achievement motivation of Class XI students of the Pontianak Cooperative Health Vocational School. The general problem of this research is how is the achievement motivation of Class XI students of the Pontianak Cooperative Health Vocational School? The sub-problems are (1) What are the characteristics of achievement motivation of class XI students of Pontianak Health Vocational School? (2) What are the achievement motivation factors for class XI students of the Pontianak Cooperative Health Vocational School? (3) How are the BK teachers' efforts in increasing the achievement motivation of class XI students of the Pontianak Cooperative Health Vocational School? The general purpose of this study was to describe the achievement motivation of class XI students at SMK Kesehatan Cooperative Pontianak. This research method is a descriptive method with a form of research that is survey research. The research subjects were students of class XI with a population of 37 students. Techniques and data collection tools used in this study were indirect communication and questionnaires. Based on the results of data analysis on the characteristics of achievement motivation of students in class XI of Cooperative Health Vocational School, Pontianak as a whole reached 79%, meaning that it was in the